Oxidation-induced activation of chalcogen bonding in redox-active bis(selenomethyl)tetrathiafulvalene derivatives. Issue 43 (14th October 2022) - Beau, Maxime; Jeannin, Olivier; Fourmigué, Marc; Auban-Senzier, Pascale; Barrière, Frédéric; Jeon, Ie-Rang
Abstract : Tetrathiafulvalene, upon its oxidation, activates Se-atoms and consequently drives a strong and directional chalcogen bonding interaction with a bromide anion. Abstract : Chalcogen bonding (ChB) interactions are investigated in two new –SeMe substituted tetrathiafulvalene (TTF) derivatives, RTTF(SeMe)2 (R = Me2, SCH2 CH2 S). Upon oxidation to 1 : 1 cationic radical salts, Se atoms are engaged in highly linear ChB interactions with bromide anions, demonstrating the efficient σ-hole activation of selenium through redox-active substituents.